Factors associated with professional healthcare advice seeking in women at risk for developing breast cancer-related lymphedema. Issue 3 (March 2018) - Sherman, Kerry A.; Kilby, Christopher J.; Elder, Elisabeth; Ridner, Sheila H.
Highlights: 6–20% of breast cancer patients who undergo axilla surgery will develop lymphedema. At-risk women should seek healthcare advice if lymphedema symptoms arise. Illness coherence, response efficacy, and distress were linked with advice-seeking. Health professionals should aim to improve patient education in these three areas. Abstract: Objectives: Approximately 6–20% of breast cancer patients undergoing lymph node surgery will develop lymphedema. At-risk individuals are encouraged to seek professional healthcare advice if symptoms arise. This study aimed to identify cognitive and affective factors associated with professional healthcare advice (PHCA) seeking behavior in women with heightened lymphedema risk. Methods: Women with increased lymphedema risk ( N  = 462) completed an online survey measuring cognitive and affective responses to lymphedema risk, including the Illness Perception Questionnaire (Revised), and adherence to seeking PHCA. Results: Overall, 62% of women reported seeking professional healthcare advice if symptoms arose. Logistic regression analysis indicated that adherence to seeking PHCA if lymphedema symptoms arise was associated with greater illness coherence, belief in the efficacy of seeking PHCA, and lymphedema risk-related emotional distress. Conclusion: Women were more likely to seek PHCA if symptoms arose if they held a coherent understanding of lymphedema and believed in the usefulness of seeking PHCA. For these women, psychological distress associated with lymphedema risk was associated with enhanced adherence to seeking PHCA. Practice implications: Health professionals should target lymphedema education to ensure at-risk women have a coherent understanding of lymphedema and that they believe in the effectiveness of seeking PHCA to help manage lymphedema symptoms.